Inhibition of SOD1 trimerization is a novel drug target for ALS disease - Tae-Gyun Woo; Jin Han; Yuju Kim; Young jun Hwang; Mua Lee; So-mi Kang; Soyoung Park; Yeongseon Ji; Yeon-Ho Chung; Songyoung Baek; Eunbyeol Shin; Minju-Kim; et al. (Translational Neurodegeneration)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that begins with motor neuron death in the spinal cord and cerebral cortex, ultimately resulting in death from respiratory distress (breathing failure). About 90% of ALS cases are sporadic, and 10% of ALS cases are of the inherited type with a genetic cause. About 150 different gene mutations have been reported so far. SOD1 is a well-identified gene associated with ALS. Indeed, SOD1 aggregation has been reported in ALS patients, but the mechanism of SOD1 aggregation remains unclear. Our previous work showed that inhibiting SOD1 aggregation with a hit compound (PRG-A-01) could reduce the SOD1-induced cytotoxicity and extend the lifespan of ALS mouse model (SOD1G93A−Tg). However, the low bioavailability and rapid degradation of the compound in vivo necessitates the development of a more effective candidate. We generated different derivatives and finally obtained the most potential drug candidate, PRG-A-04. Methods Neuronal cell lines were transfected with the mutant SOD1 expression vector and incubated with PRG-A-04. SOD1 aggregation was examined by SOD1 oligomerization assay, immunofluorescence and dot blot assay. The interaction between GST-conjugated SOD1 recombinant proteins and PRG-A-04 was identified using LC–MS/MS and GST pull-down assay. To check the in vivo therapeutic effect of PRG-A-04, SOD1G93A−Tg mice were injected with PRG-A-04; then behavioral test, histological analysis and microarray were performed. Results PRG-A-04 demonstrated favorable pharmacokinetics including high bioavailability and significant blood–brain barrier penetration. Indeed, oral administration of PRG-A-04 in ALS mouse model inhibited the aggregation of SOD1 in the spinal cord, protected against neuronal loss, and extended the lifespan of ALS mice by up to 3 weeks. In vitro, PRG-A-04 selectively bound to the mutant form of SOD1, but not the wild type, and efficiently inhibited the aggregation caused by SOD1-G147P (a SOD1 trimer stabilizer). Conclusions Our findings underscore the potential of targeting trimeric SOD1 in ALS treatment, positioning PRG-A-04 as a strong drug candidate for both familial and sporadic ALS.